Antibacterial activity of natural flavones against bovine mastitis pathogens: in vitro, SAR analysis, and computational study - Ahlam Haj Hasan; Gagan Preet; Rishi Vachaspathy Astakala; Hanan Al-Adilah; Emmanuel Tope Oluwabusola; Rainer Ebel; Marcel Jaspars (In Silico Pharmacology, 2024)
Bovine mastitis is a worldwide disease affecting dairy cattle and causes major economic losses in the dairy industry. Recently, the emergence of microbial resistance to the current antibiotics complicates the treatment protocol which necessitates antibiotic stewardship and further research to find new active compounds. Recently, phytobiotics have gained interest in being used as an alternative to antibiotics in the poultry industry as an antibiotic stewardship intervention. This study evaluated the in vitro antibacterial activity of 16 flavonoids against bovine mastitis pathogens. Two flavones: 2-(4-methoxyphenyl)chromen-4-one ( 1 ) and 2-(3-hydroxyphenyl)chromen-4-one ( 4 ) showed inhibition of the growth of Klebsiella oxytoca with MIC values range (25–50 µg mL − 1 ) followed by a structure-activity relationship (SAR) study indicating that the presence of a hydroxyl group at C-3` or methoxy at C-4` increases the activity against Klebsiella oxytoca while the presence of hydroxyl group at C-7 decreases the activity. Furthermore, a structure-based drug development approach was applied using several in silico tools to understand the interactions of active flavones at the active site of the DNA gyrase protein. Compound ( 4 ) showed a higher docking score than quercetin (standard) which is known to have antibacterial activity by inhibiting the DNA gyrase. In addition, the structure-based pharmacophores of compound ( 4 ) and quercetin showed similar pharmacophoric features and interactions with DNA gyrase. Based on our findings, compounds ( 1 ) and ( 4 ) are promising for further study as potential anti-microbial phytochemicals that can have a role in controlling bovine mastitis as well as to investigate their mechanism of action further.